ANALYSIS OF CLINICAL RISK SURGICAL SERVICES TO SUPPORT SERVICES QUALITY AT ARIFIN ACHMAD RIAU HOSPITAL - Tubagus Odih R Wahid; Dedi Affandi; Zainal Abidin; Mitra Mitra; Abdur Rahman Hamid (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2022)
Introduction: The quality of hospital services is one of the indicators. Its function as a health care provider by creating satisfaction through health services with the best quality, in its implementation will synergize with clinical risk management one of the surgical services. Purpose and Method: The purpose of research is to analyze the implementation of clinical risk management surgery in supporting the quality of hospital services, This research was conducted at Arifin Achmad Riau, with a qualitative approach to rapid assessment procedure research design through observation, in-depth interview and triangulation analysis. The number of informants as many as 8 people following the rules purposively. Results: Informed consent has been understood and filled in according to regulations, although there are sometimes unreadable and incomplete writings, but generally good with the marked lack of prosecution. Surgical Safety Checklist is good. Preoperative and postoperative diagnosis discrepancy recording and reporting sourced from the operating report sheet has been done well and understands what is meant in accordance with regulations. For the formation of the operations team is still dominated in the superior services and the implementation of consultation during operations has been well underway, although there are still constraints namely the limited availability of operating rooms and evaluation of operations team activities that have not been regularly carried out. Conclusion: Implementation of good clinical risk management implementation of surgery is proven to support the quality of service in Arifin Achmad Hospital, implementation of operations team and consultation during surgery in order to be maximized.